A general mechanistic model for predicting the fate and transport of phthalates in indoor environments. (26th November 2018) - Liang, Yirui; Bi, Chenyang; Wang, Xinke; Xu, Ying
Abstract: A mechanistic model that considers particle dynamics and their effects on surface emissions and sorptions was developed to predict the fate and transport of phthalates in indoor environments. A controlled case study was conducted in a test house to evaluate the model. The model‐predicted evolving concentrations of benzyl butyl phthalate in indoor air and settled dust and on interior surfaces are in good agreement with measurements. Sensitivity analysis was performed to quantify the effects of parameter uncertainties on model predictions. The model was then applied to a typical residential environment to investigate the fate of di‐2‐ethylhexyl phthalate (DEHP) and the factors that affect its transport. The predicted steady‐state DEHP concentrations were 0.14 μg/m 3 in indoor air and ranged from 80 to 46 000 μg/g in settled dust on various surfaces, which are generally consistent with the measurements of previous studies in homes in different countries. An increase in the mass concentration of indoor particles may significantly enhance DEHP emission and its concentrations in air and on surfaces, whereas increasing ventilation has only a limited effect in reducing DEHP in indoor air. The influence of cleaning activities on reducing DEHP concentration in indoor air and on interior surfaces was quantified, and the results showed that DEHP exposure can be reduced by frequent and effective cleaning activities and the removal of existing sources, though it may take a relatively long period of time for the levels to drop significantly. Finally, the model was adjusted to identify the relative contributions of gaseous sorption and particulate‐bound deposition to the overall uptake of semi‐volatile organic compounds (SVOCs) by indoor surfaces as functions of time and the octanol‐air partition coefficient ( K oa ) of the chemical. Overall, the model clarifies the mechanisms that govern the emission of phthalates and the subsequent interactions among air, suspended particles, settled dust, and interior surfaces. This model can be easily extended to incorporate additional indoor source materials/products, sorption surfaces, particle sources, and room spaces. It can also be modified to predict the fate and transport of other SVOCs, such as phthalate‐alternative plasticizers, flame retardants, and biocides, and serves to improve our understanding of human exposure to SVOCs in indoor environments.